Análise epidemiológica da COVID-19 na VIII Região de Saúde do Estado de Pernambuco no ano de 2020 - Silva, Eliane Oliveira da (2022)
Introduction: The second pandemic of the 21st century was declared in March 2020, caused by a new coronavirus, called SARS-CoV-2, responsible for the disease Covid-19. This virus, despite not having a high lethality, had high transmissibility, which triggered an uncontrolled spread, collapse in the health systems of several countries and strict social isolation. The knowledge on the subject sought to contribute to the management and monitoring of Covid-19 and to be an important scientific instrument. Objective: To analyze the temporal and spatial spread of Covid-19 cases in the VIII Health Region of Pernambuco as of March 2020. Methods: This is an observational, descriptive study with a temporal and cross-sectional reference. Results: In 2020, 15,205 cases of Covid-19 were confirmed, of which 95.8% were defined as mild and 4.2% as severe, mild cases were more concentrated in females and, mainly, in the 30-39 age group. , while severe cases predominated in males, especially after 50 years of age. The most populous city emerged with the highest number of cases, but did not have the highest incidence and lethality. The symptoms had a respiratory profile, especially the cases that progressed to death, and some comorbidities such as heart and vascular diseases, diabetes mellitus and arterial hypertension predominated, indicating the need for special attention for these groups. The spatial relationship demonstrated the process of internalization of the disease. Discussions: Intrinsic and extrinsic factors were determinant in the epidemiological pattern of disease propagation and in the temporal concentration of cases. Final Considerations: The Surveillance of the municipalities in the studied region is recommended: define strategies to reduce underreporting, improve the filling of the variable address of residence and carry out evaluation of data quality attributes.